Regulation Model for Collecting State Revenue in Registration of Sale and Purchase Land - Muchtar, Andhyka; Mujib, M. Misbahul (Journal of Sustainable Development and Regulatory Issues (JSDERI), 2024)
Taxes serve as the primary source of income for the nation to finance its diverse requirements. Land sales and purchase taxes are a specialized sort of tax revenue. Nevertheless, the current taxing arrangements for land transactions enforced by the state remain unjust and need more legal certainty. This study evaluates the significance of state taxation regulations in land acquisitions, aiming to establish legal certainty and justice for the community. It proposes that state taxes on land sales should be determined based on the Tax Object Proceeds Value (NJOP). It advocates for implementing a self-assessment system to ensure equitable taxation and legal certainty in Indonesia. This study employs a doctrinal legal research methodology, conceptual approach, and statutory regulations. The sources utilized encompass primary and secondary legal texts, subsequently synthesized through deductive syllogism. The results indicate that the current rules for determining state tax deductions for land sales in Indonesia are invalid and unfair. This is because they need a self-assessment system, which leads to a lack of clarity and transparency. To address this issue, it is necessary to implement the Tax Deal System as the primary method for collecting sales and purchase taxes on land. This system would allow taxpayers to communicate with tax authorities to determine the land's fair value before conducting transactions to ensure that the transaction value and tax amount are based on the actual value of the land.